Genetic Diversity of Mitochondrial DNA Cytochrome b in Indonesian Native and Local Cattle Populations - Peni Wahyu Prihandini; A Primasari; M Luthfi; J Efendy; D Pamungkas (Indonesian Center for Animal Research and Development (ICARD), 2020)
Information on the genetic diversity of native and local cattle in Indonesia is vital for the development of breeding and conservation strategies. This study was aimed to assess the genetic diversity and phylogenetic relationship of the Indonesian native (Bali) and local [(Donggala, Madura, Sragen, Galekan, Rambon, dan Peranakan Ongole Grade x Bali (POBA)] cattle populations. Genomic DNA was extracted from blood samples (n= 75). Partial sequences of mtDNA cyt b, 464 bp, were amplified using the polymerase chain reaction technique (forward primer: L14735 and reverse primer: H15149). Thirty-four reference sequences of Bos taurus, Bos indicus, and Bos javanicus were included in the phylogenetic analyses. A total of 55 polymorphic sites and 13 haplotypes were observed in the whole breeds. No variable sites of mtDNA cyt b were observed in Galekan (kept in BCRS) and Rambon cattle. Overall haplotype diversity and nucleotide diversity were 0.515 ± 0.070 and 0.0184 ± 0.0045, respectively. The highest (0.092) and the lowest (0.000) genetic distances were between Bali and Donggala cattle populations and among Galekan (kept in BCRS), Rambon, and POBA cattle populations, respectively. Both mtDNA network and phylogenetic analyses revealed two major maternal lineages (A and B) of the studied population. Most of the sampled individuals (69.33%, present in haplotype H8-H19) were linked to lineage B, which belonged to the same cluster with Bos javanicus. Overall, most of the Indonesian native and local cattle populations had a considerable genetic diversity and shared a common maternal origin with Bos javanicus.